Website Rekomendasi Tempat Kuliner dengan Metode Social Trust Path - Oloan Sihombing; Supriadi Sihombing; Marta Lena Pasaribu; Robi Kris Dinata Saragih (Jurnal Sains dan Teknologi, 2020)
Nowadays, many culinary websites have emerged which provide various information about culinary places in the city ofMedan, such as qraved and zoobo. The rating system used by these websites has weaknesses, because the websites above providerecommendations based on the rating given by other application users that are not recognized by the user, so the trust level of the ratingis very weak. Looking at the shortcomings of the websites above, this application can be made with features, such as the culinarylocation search feature based on the type of halal food and vegetarian food types. Recommended features based on culinary location,as well as distribution of halal and vegetarian foods. In the process of determining the list of recommendations, the Social Trust Pathmethod will be used. The Social Trust Path method is a method of calculating the level of trust of something depending on the level oftrust of the user who gave the statement. The tools used to do analysis and design are use case diagrams. This website is built usingPHP coding and MySQL database. The results of this study are applications for web-based culinary recommendations that can be usedto provide information on culinary places for users.